Tactical UAV Localization Using Coordinated Monopulse Trackers with Low Rate Feedback. (30th July 2013) - An, Chan-Ho; Yang, Janghoon; Ran, Rong; Pak, Ui Young; Ryu, Young-Jae; Kim, Dong Ku
To run a tactical unmanned aerial vehicle (UAV), efficient information transmission schemes, such as beamforming, are preferred due to the limit of the payload. Therefore, beam tracking and localization algorithms are considered to be one of the key technologies. In this paper, we propose a coordinated UAV localization algorithm for a tactical scenario where the ground receivers are connected with wireless limited lower rate backhaul and are closely spaced. By applying the αβ filter to the conventional scheme, we first show that the localization performance can be improved significantly. We also propose an efficient localization algorithm for a system with low rate limited feedback. Using numerical simulations, we show that the proposed scheme can improve the localization performance while reducing the feedback over conventional scheme.